PEMBUATAN TEMPAT SAMPAH PERCONTOHAN SEBAGAI UPAYA MENGATASI MASALAH SAMPAH DI DESA POLOHUNGO - Hafid, Wahyuni; Hano, Yanti Hz; Djau, Moh Fikyan (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
Polohungo village has a population of 2.025 people in six hamlets. Based on survey data on field learning experience 1 ( PBL 1) in hamlets one, two, and three. Many Polohungo villagers do not have trash cans. It can be seen that the distribution of ownership of trash bins is based on the number of households ( 38.3% ) and 121 households ( 61.7% ). And the most that do not have trash bins are in hamlet 2, which is 52 families ( 26.5% ) of the total number of families in the hamlet. The goal is to provide awareness to the public that the importance of disposing of waste in its place and also keeping the environment clean and its benefits for health. The method used is a fission intervention, namely making a pilot trash can for the community in order to increase the utilization and ownership of the trash can in every house in the village of polohungo. The results of our activities were successful in completing 3 trash bins within 4 days, although in the manufacturing process we encountered problems, such as when it rained almost every day, within 4 days we finished making trash bins, starting with looking for used drums in every hamlet, cutting, cleaning, painting up to the stage of laying drums in three hamlets in this case we were assisted by the local community, the hamlet head and also the Polohungo village youth group